Examining the Moderating Role of Brand Loyalty among Consumers of Technology Products - Ramachandran, Sunder; Balasubramanian, Sreejith (Sustainability, 2020)
The long-term survival of a company depends on its economic sustainability. It costs several times more to acquire new customers than retain current ones, and loyal customers spend more than new ones. Unfortunately, consumers are increasingly becoming less loyal to brands/products than before. Unearthing the underlying reasons for this diminishing consumer loyalty is critical. This forms the motivation of this study, which aims to examine the moderating role of loyalty among consumers of technology products. Specifically, the study explores the heterogeneity in the factors (antecedents) influencing brand-loyal attitudes and behavior among consumers of different loyalty levels. A total of 355 survey responses were obtained from an administrated survey across three loyalty groups (high loyalty—155; medium loyalty—99; low loyalty—90) in the United Arab Emirates. Structural equation modeling and multi-group moderation tests were used to test the hypothesized differences in the relationships between antecedents (trust, self-image, quality, and perceived ease of use) and customer attitude, and between customer attitude and repurchase intentions among the different loyalty groups. The results show that the different levels of loyalty have a moderating impact on the relationships. The findings are useful for marketers to better understand and manage customer attitudes, and subsequent purchase/repurchase intention depending on the levels of loyalty they may be in, as well as maneuver their customers through the different levels of loyalty to achieve business sustainability.